Cost effective design of a sealed off CO₂ gas laser - Iqbal, S.; Khan, N.; Marion, N.; Iqbal, S. J.; Bashi, S. M. (2002)
A simple but quantitatively descriptive design is presented that will helps and makes it easy for new ones, to understand and design a sealed CO₂ laser. The design of a sealed CO₂ gas laser is undertaken as a study project. Both laser. tube and power supply is housed in a specially designed container. Cooling of the laser tube and power supply is efficiently achieved by using four 30Watt fans. Sealed tube operation can be carried out in both CW and pulsed mode. The variation in the output power due to changes in electrical current and temperature has been considered. Novel design approaches are used for expediency, and cost savings.